Cultivating climate-smart crop systems: a systematic map of agronomic interventions in a Mediterranean-type climate - Buchanan, Kent; Midgley, Stephanie J.E.; Strauss, Johann; Swanepoel, Pieter (Frontiers in Agronomy, 2025)
Agriculture systems require evidence-based management approaches to minimize impacts from climate change and to minimize greenhouse gas emissions. This is critical in global regions with a Mediterranean-type climate where the impacts are expected to intensify greater than the global average, thus threatening crop yields. A significant knowledge gap exists regarding the agronomic interventions that are suitable for climate-smart agriculture considering their net effects on climate adaptation and mitigation. This study seeks to fill this gap in the context of a Mediterranean-type climate. A systematic map study was conducted on peer-reviewed research focusing on climate change relevant agronomic interventions in crop production systems. The aim was to assess the extent of the research pertaining to climate mitigation and/or climate adaptation and the readiness to inform evidence-based climate-smart agriculture policy. A total of 722 articles were identified from database searches, 648 articles were screened for relevance, and 158 articles were selected for further analysis. Information was extracted on geographic location of the research, timing of the research, type of climate change outcome researched, interventions studied, and crops studied. The study found that the knowledge base was significantly inadequate of what can be implemented to adapt and/or mitigation climate change and the net climate effects of interventions. 27 interventions were studied across 55 unique crops since 1996, mostly in Spain and Italy. More studies were relevant to climate adaptation (62%) than mitigation (22.5%). 15.2% of studies considered both adaptation and mitigation together and only 1 of 158 considered impacts on yield, adaptation, net mitigation. This study concluded that a larger evidence base is needed to inform policy on which crop management interventions are suitable to maximize positive impacts of both climate mitigation and adaptation together, with positive or acceptable yield outcomes. It is also recommended that further research into interventions should include yield and product quality, as well as economic and social benefits and trade-offs.